2008
DOI: 10.1074/jbc.m710358200
|View full text |Cite
|
Sign up to set email alerts
|

Rexinoids Modulate Steroid and Xenobiotic Receptor Activity by Increasing Its Protein Turnover in a Calpain-dependent Manner

Abstract: The steroid and xenobiotic receptor SXR (human pregnane X receptor) is a nuclear receptor that plays a key role in the body's detoxification response by regulating genes involved in drug metabolism and transport. SXR ligands include a wide range of compounds, which induce transcription of SXR target genes via activation of a heterodimeric transcription factor consisting of SXR and the related nuclear receptor retinoid X receptor (RXR). We investigated the effect of RXR-selective ligands, rexinoids, on SXR/ RXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In agreement with these observations, CoCl 2 , an agent mimicking partially hypoxia through HIF1α induction and stabilization, was found to increase UCH-L1 expression in 3T3-L1 adipocytes and to promote RXRα protein breakdown in a UCH-L1-dependent manner. RXRα is a known target of the UPS in several cell types (31)(32)(33)(34)(35), and our present data showed that RXRα was a substrate for in vitro ubiquitin conjugation, whereas RXRβ was unable to undergo this posttranslational modification. However, recombinant UCH-L1 neither modified the ubiquitin conjugation rate in the acellular system nor engaged direct protein-protein interaction with RXRα in vitro, as assayed by GST-pulldown assays (data not shown), which suggests that this enzyme promotes RXRα breakdown in an indirect manner.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In agreement with these observations, CoCl 2 , an agent mimicking partially hypoxia through HIF1α induction and stabilization, was found to increase UCH-L1 expression in 3T3-L1 adipocytes and to promote RXRα protein breakdown in a UCH-L1-dependent manner. RXRα is a known target of the UPS in several cell types (31)(32)(33)(34)(35), and our present data showed that RXRα was a substrate for in vitro ubiquitin conjugation, whereas RXRβ was unable to undergo this posttranslational modification. However, recombinant UCH-L1 neither modified the ubiquitin conjugation rate in the acellular system nor engaged direct protein-protein interaction with RXRα in vitro, as assayed by GST-pulldown assays (data not shown), which suggests that this enzyme promotes RXRα breakdown in an indirect manner.…”
Section: Discussionmentioning
confidence: 69%
“…Rxr mRNA levels were similar in WAT of OB/OB and ob/ob mice fed a regular diet (LFD) or high-fat diet (HFD). However, RXRα activity has previously been shown to be regulated by protein degradation in several cell types (31)(32)(33)(34)(35). We thus investigated whether RXRα polypeptide stability is affected in visWAT and scWAT of OB/OB and ob/ob mice.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a number of reports documented the proteasomal degradation of RXRα in various cellular backgrounds 37 , which appeared to be conditioned by RXR interaction with RAR and the corepressor SMRT 38,39 and increased upon agonist binding 40,41 . Moreover, RXRα breakdown is dependent on MAPK or PKC activity 42,43 , hinting at a link between RXRα phosphorylation and proteasomal-mediated degradation 44 .…”
Section: 5mentioning
confidence: 95%
“…Many nuclear receptors are regulated by modulation of protein expression. 29,30 Therefore, we also investigated whether As 2 O 3 decreased LXR␣/ LXR␤ protein expression. Immunoblotting experiments, using extracts from RAW 264.7 and THP-1 cells treated with 22R-OHC/9-cis-RA in the absence or presence of 1 to 5 mol/L of As 2 O 3 , showed no significant alteration of LXR␣/LXR␤ protein levels (Supplemental Figure IIB).…”
Section: As 2 O 3 Does Not Alter Nuclear Receptor Expression or Hetermentioning
confidence: 99%